Philanthropy, politics and promotion: Philip Morris' "charitable contributions" in Thailand. Issue 4 (24th July 2008) - MacKenzie, Ross; Collin, Jeff
Abstract : The efforts of members of the tobacco industry to portray themselves as responsible corporations via ostensible commitment to improved labour practices and public philanthropy have attracted growing criticism. This is particularly true of corporate social responsibility (CSR) schemes undertaken in emerging nations that are designed to rehabilitate the tobacco industry's image among public, government and market opinions in North America and western Europe. In the case of Thailand, sponsorship of arts events and community groups has been one avenue of promoting the industry in a regulatory environment that severely curtails promotion and advertising. The Association of Southeast Asian Nations (ASEAN) Art Award, sponsored by Philip Morris (PM) has provided one such outlet for 10 years. Analysis of PM funding announcements since the end of the ASEAN art programme in Thailand reveals that recent donations to tobacco-related community organisations reinforces the extent to which seemingly generous acts are driven by corporate self-interest rather than social responsibility.